PELATIHAN CARA MENDESKRIPSIKAN RUMAH DALAM BAHASA INGGRIS BAGI SISWA KELAS X JURUSAN BISNIS KONSTRUKSI DAN PROPERTI DI SMK NEGERI JAWA TENGAH SEMARANG - Ratna Asmarani; Cut Aja Puan Ellisafny; Hadiyanto Hadiyanto (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
The skill to be able to write a good house description in English is useful for those involving in housing property. This opinion triggers the team of Community Service of English Department, Faculty of Humanities, Diponegoro University, to carry out a short training on How to Describe Houses in English for the students of grade X at SMK Negeri Jawa Tengah (Central Java State Vocational High School) in Semarang majoring in Construction and Property Business. The method used in the short training is the Bi-lingual Method which combines Bahasa Indonesia as the mother tongue and English as the language learned. The training on descriptive writing is divided into three sessions: presentation of the materials, discussion consisting of questions-answers, and guided practice. The result of the short training shows that the students are so enthusiastic in following the whole session because the materials are familiar to them, the method is not burdening, and they have a chance to develop their descriptive writing skill. It can be concluded that short but efficient trainings in line with the students’ major need to be conducted more often to give them extra practical skills useful for them to face the real work world. Keywords: house description, descriptive writing, bi-lingual method, SMK Negeri Jawa Tengah